1‐Indanone and 1, 3‐indandione Derivatives as Ligands for Misfolded α‐Synuclein Aggregates. (8th November 2021) - Sun, Xianwei; Admane, Prasad; Starosolski, Zbigniew A.; Eriksen, Jason L.; Annapragada, Ananth V.; Tanifum, Eric A.
Abstract: The development of imaging agents for in vivo detection of alpha‐synuclein (α‐syn) pathologies faces several challenges. A major gap in the field is the lack of diverse molecular scaffolds with high affinity and selectivity to α‐syn fibrils for in vitro screening assays. Better in vitro scaffolds can instruct the discovery of better in vivo agents. We report the rational design, synthesis, and in vitro evaluation of a series of novel 1‐indanone and 1, 3‐indandione derivatives from a Structure‐Activity Relationship (SAR) study centered on some existing α‐syn fibril binding ligands. Our results from fibril saturation binding experiments show that two of the lead candidates compounds 8 and 32 bind α‐syn fibrils with binding constants (Kd ) of 9.0 and 18.8 nM, respectively, and selectivity of greater than 10× for α‐syn fibrils compared with amyloid‐β (Aβ) and tau fibrils. Our results demonstrate that the lead ligands avidly label all forms of α‐syn on PD brain tissue sections, but only the dense core of senile plaques in AD brain tissue, respectively. These results are corroborated by ligand‐antibody colocalization data from Syn211, which shows immunoreactivity toward all forms of α‐syn aggregates, and Syn303, which displays preferential reactivity toward mature Lewy pathology. Our results reveal that 1‐indanone derivatives have desirable properties for the biological evaluation of α‐synucleinopathies. Abstract : Homing in on the ideal α‐synuclein ligand ! The effective diagnosis of specific neurodegenerative disorders is complicated by the accumulation of multiple misfolded amyloid species in their pathogenesis. High‐affinity and selective probes toward specific amyloid aggregates are imperative. SAR studies on some existing α‐synuclein ligands have resulted in leads with high affinity and selectivity toward α‐syn versus Aβ and tau aggregates.